Behavioural Studies on Andaman Green Imperial Pigeon in Captivity - Het, Ram; Sinha, A. K.; Misra, J. P. (Indian Forester, 1993)
Andaman green imperial pigeon is endemic to Andaman group of Islands and is kept under Schedule-I of Wildlife (Protection Act), 1972. Study has been made on its feeding behaviour, flying behaviour, drinking behaviour, nest building behaviour and preening behaviour.